Medical physics during the COVID-19 pandemic : global perspectives in clinical practice, education and research - Ng, Kwan-Hoong; Stoeva, Magdalena S. (Boca Raton, FL : CRC Press, 2021)
Spreading to every corner of the Earth, the COVID-19 virus has had an unparalleled impact on all aspects of our lives. This book explores in detail how the COVID-19 pandemic has affected clinical practice, education, and research in medical physics, and how colleagues on the frontline dealt with this unpredictable and unprecedented pandemic. It tackles key questions such as: How did medical physicists first respond to the situation? What innovative strategies were taken and how effective were they? How are medical physicists preparing for the future? There will be a focus on the different experiences of regional medical physicists and the responses and outlooks in clinical practice, education, and research in the affected continents, Asia-Pacific, the Middle East, Europe, Africa and North and Latin America. With over 91 contributors from 39 countries, this unique resource contains key perspectives from teams from each territory to ensure a global range of accounts. The collective opinion and wisdom from the major medical physics journal editors-in-chief are also explored, alongside how the pandemic has affected the quantity and quality of publications. Voices of early-career researchers and students of medical physics will be included, with narratives of their experiences coping with life during the pandemic. Lastly, communicating leadership in times of adversity is highlighted. This book will be a historic account of the impact of the COVID-19 virus on the field of medical physics. It will be an ideal reference for medical physicists, medical physics trainees and students, hospital administrators, regulators, and healthcare professionals allied with medical physics. Key features: The first book to cover the impact of COVID-19 on the field of medical physics Edited by two experts in the field, with chapter contributions from subject area specialists around the world Broad, global coverage, ranging from the impact on teaching, research, and publishing, with unique perspectives from journal editors and students and trainees
OCLC-licensed vendor bibliographic record.
Keywords: Medical physics -- Cross-cultural studies; COVID-19 (Disease) -- Cross-cultural studies; SCIENCE / Radiology; MEDICAL / Infectious Diseases; MEDICAL / Allied Health Services / Emergency Medical Services